Vitreoscilla filiformis Extract for Topical Skin Care: A Review - Gueniche, Audrey; Liboutet, Muriel; Cheilian, Stephanie; Fagot, Dominique; Juchaux, Franck; Breton, Lionel (Frontiers in Cellular and Infection Microbiology, 2021)
The term probiotic has been defined by experts as live microorganisms, which when administered in adequate amounts, confer a health benefit on the host. Probiotics are thus, by definition, live microorganisms and the viability of probiotics is a prerequisite for certain benefits : such as the release of metabolites at the site or adhesion properties for example. However, some semi-active or non-replicative bacterial preparations may retain similar activity to the live forms. On cosmetic lysates or fractions are generally used. Topically applied Vitreoscilla filiformis extract has shown to have some similar biological activity of probiotics in the gut, for example, regulating immunity by optimisation of regulatory cell function, protecting against infection and helping skin barrier function for better recovery and resistance. Due to their mode of action and efficacy, V. filiformis extract (lysate including membrane and cytosol) may be considered as non-replicative probiotic fractions, this review article presents all its properties.